Factors Associating with the Segmental Postural Control during Sitting in Moderate-to-Late Preterm Infants via Longitudinal Study - Noppharath Sangkarit; Wantana Siritaratiwat; Surussawadi Bennett; Weerasak Tapanya (MDPI AG, 2021)
(1) Background: biological variables and particular child rearing practices could be linked to postural control and rates of sitting onset. The segmental Assessment of Trunk Control (SATCo) is currently used as an assessment of postural control with a specific segment on premature infants. However, the association between related factors and segmental trunk control during sitting development in preterm infants via longitudinal assessments is still limited. Objective: to investigate the associations between biological and child rearing factors and segmental trunk control during sitting in moderate to late premature birth from the age of 4 months to age of independent sitting attainment. (2) Methods: forty-two infants born between 32 and 36 weeks of gestation were recruited. Their segmental trunk control was assessed using the SATCo. Their related factors were recorded from the age of 4 months to early onset of independent sitting attainment. The generalised estimating equation (GEE) model was used to identify the association between related factors and the SATCo with a linear distribution. (3) Results: cause of prematurity, baby rocking recliner and baby walker usage were negative factors, while play in a sitting position, opportunity to move on a traditional mat and sleep mattress were positive factors contributing to the segmental control of the trunk. (4) Conclusions: the experience of sitting on different surfaces and an opportunity to sit without support during the child rearing period from age of 4 months corrected could be positive factors associating with the segmental trunk control in moderate-to-late premature infants.